MEMBANGUN JARINGAN ULAMA YANG DITERAPKAN DALAM GERAKAN MUHAMMADIYAH - Silawati, Silawati; Nurdiniyah, Hayyun (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
The Ulama network is a journey to seek knowledge that is very closely related to scientific traditions. This tradition originates from the scientific journey of the companions after the death of the Prophet to collect and record hadith. Developments seen from scientific journeys not only provided a collection of the Prophet's Hadith, but also encouraged a "network" of the Prophet's companions who took part in recording, memorizing and recording hadiths. The need for a modern Muhammadiyah Islamic renewal movement in facing challenges in the era of globalization and advances in science and technology. The method used is descriptive analytical method with a historical approach, as a problem study methodology framework that aims to look at all problems in the past. This approach makes it easy to understand the reasons that led to the emergence of the modern Muhammadiyah Islamic thought movement in Indonesia